Bacterial Pathogen Responsible For Urinary Tract Infection. - Chaudhary, Raina; Ojha, Chet Raj; Sijapati, Khagendra; Singh, Sunil Kumar (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Urinary Tract Infection (UTI) is one of the common medical conditions which seek the help of clinician and prompt intervention with suitable antibiotics to prevent morbid conditions. Therefore, identification of causative agent with their antibiotic sensitivity pattern is always mandatory for successful treatment of the cases. The main objective of the study was to identify the common bacterial pathogen responsible for causing Urinary Tract Infection with determination of sensitivity pattern of commonly used antibiotics. Methods: A total of 8270 urine samples were collected from the patient attending Outpatient Department and admitted as Inpatient in ward during the period of January 2011 to December 2011 in Shree Birendra Hospital. The samples were subjected to culture for identification of pathogen with their antibiotic sensitivity pattern following standard methodology. Results: Out of total, only1654 (20%) showed growth of pathogenic organisms. Among them positivity was highest in patient attending Outpatient Department. Eight different species of bacteria was isolated as causative agent. Among them Escherichia coli (67%) was predominantly higher in number followed by Proteus spp (22.24%), Klebsiellaspp (4.07%), Pseudomonas aeruginosa(2.7%) and Citriobacterfreundii (2.3%). Among these organisms sensitivity was highest towards Amikacin (86%) & Gentamycin (69%) followed by Nitrofuranti on (60.5%). Conclusions: Causative agent of Urinary Tract Infection may vary in different situation. Definite identification of pathogen with their antibiotic sensitivity pattern is always key point for success of treatment. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/13-16 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7760